2020
DOI: 10.1007/s00226-020-01230-0
|View full text |Cite|
|
Sign up to set email alerts
|

Mineral-based composition with deliquescent salt as flame retardant for melamine–urea–formaldehyde (MUF)-bonded wood composites

Abstract: A flame retardant composition (FRC) composed of a surface-treated calcium carbonate-based mineral, having high porosity and loaded with deliquescent calcium chloride, was assessed for its potential as a flame retardant. Two FRCs with 16% and 26% calcium chloride (dry solid) stored in the pore structure, respectively, were studied with respect to their ability to absorb and release free water and their efficacy in melamine-urea-formaldehyde (MUF)bonded wood composites was investigated. Water absorption capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…Hydroxyapatite‐based mineral consisting of 59 wt% of hydroxyapatite (HA) Ca 5 (PO 4 ) 3 (OH) and about 41 wt% calcium carbonate (CaCO 3 ) was provided by Omya International AG. The detailed characteristics of the material are provided in Ozyhar et al 19 …”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Hydroxyapatite‐based mineral consisting of 59 wt% of hydroxyapatite (HA) Ca 5 (PO 4 ) 3 (OH) and about 41 wt% calcium carbonate (CaCO 3 ) was provided by Omya International AG. The detailed characteristics of the material are provided in Ozyhar et al 19 …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the industrial feasibility of this approach has been demonstrated in fiberboard products 18 . A promising mineral‐based fire‐retardant composition (FRC), consisting of a mineral carrier material and deliquescent salt for application in particle‐based wood composites has been further evaluated 19 . The authors demonstrated the efficacy of the mineral‐based FRC as a fire extinguisher and that the FRC can be easily incorporated into the structure of a particle‐based wood material.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations